EVALUASI PROSEDUR PEMBELIAN PERSEDIAAN BARANG CONSUMABLE PADA PT XYZ - Salsabila Riken Qanita; Sugeng Riadi (ABEC Indonesia, 2021)
The focus of this study is the evaluation of the procedure for purchasing consumable goods at PT XYZ. Evaluation of the purchasing procedure is carried out in order to find out whether the procedure has been carried out in accordance with the SOP set by the company or not, as well as knowing the cause of the difference in inventory. The research method of this study report is descriptive qualitative research. The research results of this study report can be concluded that the procedures carried out are in accordance with the SOP set by the company, but there are still human errors that can hinder the process of purchasing inventory and checking the receipt of ordered goods.